Groși, Maramureș: An Attractive Destination during the Covid-19 Pandemic? - COROȘ, Monica Maria; BODE, Oana Ruxandra; SĂVAN, Emanuel-Emil; BERCI, Maria Carmina (Studia Universitatis Babeș-Bolyai Negotia, 2024)
Article history: Received: February 16, 2024; Reviewed: March 29, 2024; Accepted: June 21, 2024; Available online: June 30, 2024. In Romania, the COVID-19 pandemic determined the development of rural areas and consequently, the evolution of rural tourism, one of the most important contributors to sustainable tourism. The current study examines the rural tourism potential of a village in North-Western Transylvania (Romania), Groși. The main goal of this study is to evaluate the potential for sustainable growth by means of rural tourism in this commune. This assessment also considers the potential impact on the social and economic aspects of the destination, as well as the factors that could positively or negatively influence this entire process. The data was gathered using the survey-based inquiry. Therefore, a questionnaire including 32 questions, consisting of three parts in all, was developed. The first part included questions used by the researchers aimed to gather information regarding the respondents’ orientation towards remote rural destinations. The second part of the questionnaire was designed with the end goal of establishing to what extent the respondents are familiar with the resources of Groși, respectively to assess to what extent the destination can benefit from the development of hospitality services. The last part of the survey enabled researchers to collect identification data regarding the 117 respondents of the self-implemented survey. The main conclusions of the study highlight that respondents are mostly pleased or very satisfied regarding rural tourism in the region under analysis. Among the benefits that certainly are to everyone’s liking were found to be tranquility, beautiful landscapes, fresh air, important sights, and local gastronomy. In the end, the main disadvantages of the area and the opportunities of developing rural tourism in Groși commune are presented. JEL classification: L83, Z32, L80.